INTEGRATED FARMING SYSTEM – FARMERS PERCEPTION IN TELANGANA - D. SRINIVASA CHARY, S. KAVITHA, G.SAMUEL, I. SREENIVASA RAO M.GOVERDHAN and (The Journal of Research, PJTSAU, 2021)
The present study was conducted to find out and analyze the benefits of IFS obtained by the farmers. An exploratory research design was adopted for the study during 2017-19. The total sample size was 180 IFS farmers. Data was collected through well-structured interview schedule. The results of the study revealed that increased input use efficiency (100.00%) andmaintenance of soil fertility (96.67%) ranked top among the farm benefits while increased productivity of agriculture and allied enterprises (86.67) and year round income generation (83.33 %) ranked top among the personal benefits. Increased productivity of agriculture and allied enterprises (86.67 %), year round income generation (86.67 %) and decreased cost of cultivation (80%) topped among the economic benefits. Reduction in waste material from different farm outputs (83.33 %) topped among environmental benefits and less risk of failure of crops and allied enterprises (80 %) topped among the complimentary benefits.